AN ANALYSYS ABOUT STUDENTS’ TROUBLES IN ACQUISITION ENGLISH VOCABULARY - Herri Susanto (UIBU, 2021)
The aims of the analysis titled a Study on Students' troubles for acquiring vocabulary comprised to look for out characters and elements by educates' troubles in finding out vocabulary. The topic of this study was the scholars of the primary semester of STITEK Bontang who took English class. This study applied a qualitative enquiry intent, applying features of a case study. For acquiring the information, the man of scientific discipline put-upon interview and questionnaire. All the data comprised examined descriptively. The determinations displayed that the students still faced the effects or troubles in vocabulary learning. Diverseness’s from troubles faced of students incoming vocabulary acquiring followed several. Kinds of troubles faced along the students were (1) most of the students have difficulties in saying the words, (2) a way to write and spell, (3) the various grammatical type of a word called inflections was one in all gets of learners troubles in determining vocabulary. In increase, (4) the students found difficulties in selecting the suitable that means of the words and (5) additionally still confuse in victimization the word supported the context. The last, (6) the students were also still confuse once they found discussions or aspect that comprised idiomatical. At that place bear made up some factors in that made students' troubles in acquiring vocabulary (1) the written kind is completely different from the spoken form in English, (2) The number of words that students got to learn is passing large, (3) the restrictions of sources of data regarding words, (4) The complexness of word cognition. Deliberate a words regards kind of more than acknowledging its wordbook definition, (5) lack of inferring of grammatical of the words, (6) the erroneous pronunciation is commonly caused by the dearth of sound law of similarity between English language and also the students' indigent language.